Determination of Wear Rate Equation and Estimation of Residual Life of 155mm Autofrettaged Gun Barrel - J Jain; S Soni; D Sharma (International Journal of Multiphysics, 2016)
Wear of steel at high temperature is a complex phenomenon. Quantification of wear per event is an important aspect in assessing life of a component. Necessity of economics and light weighted components compels to study the system under common parameters and extrapolate the results. Temperatures/pressures inside a gun are impossible to be measured by direct methods. Mathematical modeling and comparison of results with end effect measurable parameters is only way to predict it's accuracy.